The Implementation of Spiritual Capital Saab Mote Craftsmen: Study of The Hindu Teachings (Study of Saab Mote Craftsman in Nagasepaha Village, Buleleng) - Ni Wayan Novi Budiasni; Ni Made Sri Ayuni; Ni Kadek Ayu Trisnadewi3 (Universitas Pendidikan Ganesha, 2019)
This study focused on implementing spiritual capital in the business of beads in Nagasepaha Village, Buleleng, which was studied using the concept of understanding the values of the teachings of Hinduism ethics (moral), harmony (Tri Hita Karana), virtue (dharma) Qualitative methods of gathering Observations, interviews and documentation data were carried out to obtain results and answer the research problem formulation. The concept of Tri Hita Karana that does not neglect harmony, is that the implementation of spiritual capital in the business of the most basic implicit. Merely and is not concerned with the material (capitalism), the which shows that there is ethics (moral), so as to create dharma (virtue) the which is the result of spiritual capital